The role of UN Women in empowering women and enhancing community security (Al-Mostansiriyah journal for Arab and international studies, 2026)
Talking about the existence of community security is linked to the existence of stability and the absence of fear in the presence of a security system with integrated political, social and economic dimensions. In light of the world's recognition of the multiple sources of threats to this security, it has become important to protect and empower one of its most important pillars, which is women. Women are a fundamental partner in enhancing the process of construction and development in the present and the future. Based on this, the United Nations Entity for Gender Equality and the Empowerment of Women was the leader in efforts to support and empower women in society, and to confront the various sources of undermining their role. Realizing that women will not be able to contribute to enhancing community security if they feel that they do not live in internal peace, and that their relationship with themselves and their surroundings is not dominated by feelings of satisfaction, reassurance, security and lack of fear of the future, this research came to stand on the role of the United Nations Entity for Gender Equality in empowering women and its impact on enhancing community security.Keywords: UN Women, United Nations, violence against women, women's empowerment, community security